The convergent effects of primary school physical activity, sleep, and recreational screen time on cognition and academic performance in grade 9 - Ramer, Jared Donald; Santiago-Rodríguez, María Enid; Vukits, Amanda Joan; Bustamante, Eduardo Esteban (Frontiers in Human Neuroscience, 2022)
Lab-based experiments and randomized controlled trials consistently demonstrate improvements in youth cognition following physical activity (PA), while cross-sectional studies suggest that sedentary behavior (especially recreational screen time [RST]) and poor sleep are inversely related to cognition. However, little is known about how these 24-hour movement behaviors—sleep, PA, and sedentary behavior—converge to affect youth cognition. Therefore, the purpose of this study is to test the associations between childhood 24-hour movement behaviors and adolescent cognition using a longitudinal design and examine moderating effects of each behavior. This study utilized structural equation modeling with data from the NICHD Study of Early Child Care and Youth Development (N=1,364, 52% female, 80% White). Independent variables—sleep, RST, and PA—were collected in grade 5. Dependent variables of cognitive and academic performance were collected at grade 9; included the Stroop task, Woodcock-Johnson, and Tower of London. Grade 5 PA was inversely associated with grade 9 cognition, but this relationship was no longer significant once grade 5 cognition was controlled for in analyses. Grade 5 sleep was positively related with grade 9 cognition, whether baseline cognition was controlled for or not. Finally, grade 5 RST was inversely related to cognition and academic performance, regardless of whether baseline values were controlled. Moderation analyses showed the relationship between grade 5 RST and grade 9 cognition was moderated by grade 5 PA, while the relationship between grade 5 PA and grade 9 cognition was moderated by grade 5 sleep. In each case, more PA and sleep blunted the negative relationships.. These findings extend evidence that greater sleep promotes cognition and greater RST impairs cognition, by affirming these relationships over a longer period. They extend the evidence by demonstrating that the longitudinal relationship between individual 24-hour movement behavior and cognition are moderated by other behaviors.